Associations Between Sleep Quality and Health Span: A Prospective Cohort Study Based on 328,850 UK Biobank Participants - Sambou, Muhammed Lamin; Zhao, Xiaoyu; Hong, Tongtong; Fan, Jingyi; Basnet, Til Bahadur; Zhu, Meng; Wang, Cheng; Hang, Dong; Jiang, Yue; Dai, Juncheng (Frontiers in Genetics, 2021)
Objective: To examine the associations between sleep quality and healthspan using a prospective cohort design based on the UK-Biobank (UKB). Materials and methods: This longitudinal cohort study enrolled 328,850 participants aged between 37 and 73 years old from UK Biobank to examine the associations between sleep quality and risk of terminated healthspan. End of healthspan was defined by eight events strongly associated with longevity (cancer, death, congestive heart failure, myocardial infarction, chronic obstructive pulmonary disease, stroke, dementia and diabetes), and a sleep score was generated according to five sleep behavioral factors (sleep duration, chronotype, sleeplessness, daytime sleepiness and snoring) to characterize sleep quality. The hazard ratio (HR) and 95% confidence intervals (CI) were calculated by multivariate-adjusted cox proportional hazard model. Moreover, we calculated population attributable risk percentage (PAR%) to reflect the public health significance of healthy sleep quality. Results: Compared with the poor sleep quality, participants with healthy sleep quality had a 15% (HR: 0.85, 95%CI: 0.81-0.88) reduced risk of terminated healthspan, and those of less-healthy sleep quality had a 12% (HR: 0.88, 95%CI: 0.85-0.92) reduced risk. Linear trend results indicated that risk of terminated healthspan decreased by 4% for every additional sleep score. Nearly 15% (PAR%: 15.30, 95%CI: 12.58-17.93) of terminated healthspan in this cohort would have been prevented if healthy sleep behavior pattern was adhered. Conclusions: Healthy sleep quality was associated with reduced risk of premature end of healthspan, suggesting healthy sleep behavior may extend healthspan. However, further studies are suggested for confirmation of causality and potential mechanism.